Dietary β-galactomannans have beneficial effects on the intestinal morphology of chickens challenged with Salmonella enterica serovar Enteritidis. Issue 1 (1st January 2015) - Brufau, M. T.; Martín-Venegas, R.; Guerrero-Zamora, A. M.; Pérez-Vendrell, A. M.; Vilà, B.; Brufau, J.; Ferrer, R.
Abstract: Salmonella enterica serovar Enteritidis is one of the leading causes of food-borne salmonellosis in humans. Poultry is the single largest reservoir, and the consumption of incorrectly processed chicken meat and egg products is the major source of infection. Since 2006, the use of antibiotics as growth promoters has been banned in the European Union, and the dietary inclusion of β-galactomannans (βGM) has become a promising strategy to control and prevent intestinal infections. The aim of this study was to investigate the effect of various βGM-rich products on intestinal morphology in chickens challenged with Salmonella Enteritidis. To assess this effect, a total of 280 male Ross 308 chickens were studied (40 animals per treatment housed in 5 cages). There were 7 treatments, including controls: uninoculated birds fed the basal diet (negative control) and inoculated birds fed the basal diet (positive control) or the basal diet supplemented with Salmosan (1 g/kg), Duraió gum (1 g/kg), Cassia gum (1 g/kg), the cell walls of Saccharomyces cerevisiae (0.5 g/kg), or the antibiotic colistine (0.8 g/kg). The birds were fed these diets from the d 1 to 23, except the animals in the colistine group, which were fed the diet containing the antibiotic only from d 5 to 11. The inoculated animals were orally infected on d 7 with 10 8 cfu of Salmonella Enteritidis. Bird performance per replicate was determined for the whole study period (23 d), and the distal ileum and cecal tonsil of 5 animals per treatment (1 animal per replicate) were observed at different magnification levels (scanning electron, light, and laser confocal microscopy). In the images corresponding to the treatments containing βGM we observed more mucus, an effect that can be associated with the observation of more goblet cells. Moreover, the images also show fewer M cells, which are characteristic of infected animals. Regarding the morphometric parameters, the animals that received Duraió and Cassia gums show greater ( P = 0.001 and P = 0.016, respectively) villus length compared with the animals in the positive control, thus indicating the capacity of these products to increase epithelial surface area. However, no effect ( P > 0.05) on microvillus dimensions was detected. In conclusion, the results obtained indicating the beneficial effects of these βGM on intestinal morphology give more evidence of the positive effects of these supplements in poultry nutrition.